2020
DOI: 10.1002/qj.3886
|View full text |Cite
|
Sign up to set email alerts
|

Observational analysis and simulations of a severe hailstorm in northeastern Italy

Abstract: Hailstorms are relatively frequent in the Friuli Venezia Giulia region, northeastern Italy and, for that reason, a network of manual hailpads has been set up there since the late 1980s. On July 4, 2007, a record number of hailpads in the network were impacted by hail (115 out of about 360 total stations). To the best of the authors' knowledge, no other single hailstorm case‐study has information coming from such a large number of hailpads impacted by hail. These hailpads are analysed using automatic software, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 59 publications
2
8
0
Order By: Relevance
“…These findings are consistent with Cui et al (2023) who showed that COSMO tends to produce too many small hailstones and not enough larger ones compared to MESHS radar product. To summarize the results, HAILCAST, whether integrated in WRF or COSMO, is able to reproduce observed hail swaths over the Alpine-Adriatic region as already reported by previous studies (Trefalt et al, 2018;Manzato et al, 2020;Raupach et al, 2021;Malečić et al, 2022;Tiesi et al, 2022;Cui et al, 2023). Further by comparing the simulated and observed maximum hailstone diameters, we find that both models tend to overestimate the maximum hailstone size compared to the Croatian hailpad network.…”
Section: Hailcast Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…These findings are consistent with Cui et al (2023) who showed that COSMO tends to produce too many small hailstones and not enough larger ones compared to MESHS radar product. To summarize the results, HAILCAST, whether integrated in WRF or COSMO, is able to reproduce observed hail swaths over the Alpine-Adriatic region as already reported by previous studies (Trefalt et al, 2018;Manzato et al, 2020;Raupach et al, 2021;Malečić et al, 2022;Tiesi et al, 2022;Cui et al, 2023). Further by comparing the simulated and observed maximum hailstone diameters, we find that both models tend to overestimate the maximum hailstone size compared to the Croatian hailpad network.…”
Section: Hailcast Resultssupporting
confidence: 79%
“…Several recent studies employed HAILCAST embedded in high-resolution numerical models, such as WRF or COSMO, to study hailstorms occurring over the United States and Europe. The studies found that the models can reproduce the atmospheric conditions and triggering mechanisms responsible for hailstorm formation, resulting in simulating comparable hailstorms to those observed over the complex terrain of the United States (Adams-Selin & Ziegler, 2016; Adams-Selin et al, 2019), Switzerland (Trefalt et al, 2018;Raupach et al, 2021;Cui et al, 2023), Italy (Manzato et al, 2020;Tiesi et al, 2022), and Croatia (Malečić et al, 2022).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…For each case study reported in Table 1, the survey time of the retrieval of the SAR wind determines the time of the LAPS analysis, which is used as initial condition for the WRF model simulations. The twenty selected case studies cover a wide range of atmospheric scenarios, including episodes characterized by flow over complex orography Dudhia, 2012, 2013;Gómez-Navarro et al, 2015) conducive to episodes of orographic convection, which occasionally occur in this area (e.g., Manzato et al, 2020). The numerical experiments are performed over the geographical domain shown in Figure 1A, using a twodomain one-way-nested configuration, where d01 and d02 are the external and internal domain, respectively.…”
Section: Wrfmentioning
confidence: 99%
“…On the other hand, when the incoming marine flow is conditionally unstable, the blocked flow situation persists, resulting in low-level convergence well upstream of the orography (Fig. 3) that may evolve in the development of deep convection ("Upstream" HPEs in Davolio et al, 2016) or even mesoscale convective systems (Davolio et al, 2009;Ricchi et al, 2021) and supercells (Manzato et al, 2015;Miglietta et al, 2016), which produce heavy rainfall and hail over the plain, even close to the coastal areas (Manzato et al, 2020). In this category (e.g., IOP18), characterized by high values of the Froude number, other parameters defined by the vertical profile provide an indication of the possible evolution and severity of the event.…”
Section: North-eastern Italymentioning
confidence: 99%